2018
DOI: 10.1080/13504851.2018.1542117
|View full text |Cite
|
Sign up to set email alerts
|

Does homeownership promote wealth accumulation?

Abstract: It is well known that homeowners are richer than renters, even after controlling for observable characteristics. This is often used as an argument for policies that foster homeownership. However, the causal link between homeownership and wealth is difficult to establish due to many potential sources of endogeneity. Utilizing the Household Finance and Consumption Survey for the Euro area, we correct for endogeneity by using inheriting the household's main residence as an instrument. The exclusion restriction is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…(Bivens, 2015; Adam and Tzamourani, 2016; Bunn et al ., 2018; Lenza and Slacalek, 2018). As this finding is partly driven by the share of households in GB with no housing assets at all (around 25% according to our estimates), it adds to the policy relevant literature suggesting that the promotion of home ownership for lower wealth groups should lead to lower wealth inequality (see, Kaas, Kocharkov and Preugschat (2019)).…”
Section: Resultssupporting
confidence: 63%
“…(Bivens, 2015; Adam and Tzamourani, 2016; Bunn et al ., 2018; Lenza and Slacalek, 2018). As this finding is partly driven by the share of households in GB with no housing assets at all (around 25% according to our estimates), it adds to the policy relevant literature suggesting that the promotion of home ownership for lower wealth groups should lead to lower wealth inequality (see, Kaas, Kocharkov and Preugschat (2019)).…”
Section: Resultssupporting
confidence: 63%
“…Still, such findings are not conclusive; McCabe (2016) suggest that the contribution of homeownership to civic engagement as marginal while Aaronson (2000) suggests that even with residential stability, life events experienced by homeowners could force them to move. Further, although homeownership assumes an important place in an individuals' life due to a myriad of possibilities associated with it, more recent studies showed that the homeownership rate has been declining (Bourassa, Shi 2017;Ceritoglu 2019;Kaas et al 2019). For example, Kaas et al (2019) showed that owning a home reduces the net holdings of financial and other real wealth suggesting a negative effect of homeownership on household wealth.…”
Section: Homeownership Prior To Migrationmentioning
confidence: 99%
“…Further, although homeownership assumes an important place in an individuals' life due to a myriad of possibilities associated with it, more recent studies showed that the homeownership rate has been declining (Bourassa, Shi 2017;Ceritoglu 2019;Kaas et al 2019). For example, Kaas et al (2019) showed that owning a home reduces the net holdings of financial and other real wealth suggesting a negative effect of homeownership on household wealth. Further, Ceritoglu (2019) showed that the global financial crisis led to rise house price with compared to rent revealing a lower rent inflation, which encourages households to remain as renters suggesting a decrease in the profitability of investing in housing.…”
Section: Homeownership Prior To Migrationmentioning
confidence: 99%